Wheat antioxidants: understanding changes of phenolic profiles in the wheat food chain and developing rapid quantification methods - Tian, Wenfei (Kansas State University, 2021)
The health benefits of whole wheat foods can partially be attributed to the phytochemicals. In recent years, driven by humanity’ desire for healthier food sources, potential health benefits of wheat grains have become significant quality parameters. The goal of this study is to understand the changes in phenolic acid profiles and antioxidant potential in the wheat food chain and develop novel spectroscopy methods for rapid quantification of total phenolics in whole wheat. Specific objectives are to: 1) understand the effect of wheat varieties, environment, fertilizer, integrated managements, and their interactions on wheat phenolics; 2) investigate the effect of grain and food processing such as germination, fermentation, and baking; 3) examine potential bioaccessibility of wheat phenolics in the human digestive tract and release of phenolics by gut microbiota fermentation; and 4) develop models based on UV-Vis and NIR spectroscopies and chemometrics for rapid quantification of total phenolic content (TPC) in wheat. The study on phenolic profiles of 12 Kansas winter wheat varieties showed that most wheat phenolics (> 90%) existed in insoluble-bound forms, and phenolic content and composition were highly dependent on the varieties. The study on year, variety, and fertilizer effect indicated that the year effect was significant for TPC and most phenolic acids. Increased nitrogen application led to increased production of trans-ferulic acid, and sulfur application affected the response to nitrogen application. Varieties also differed in the response of phenolic acid concentration and composition to sulfur application. Results also showed that year x location x management and year x management x variety interactions were significant for TPC. Year x location x variety x management was significant for most phenolic acids. Managements with no fungicide application may lead to increased accumulation of phenolic compounds, especially for varieties that are more susceptible to the fungi infection. Due to significant effect from varieties, different varieties were included in the studies of processing effects. Seed germination at early-stage (<24 h) did not influence baking properties of whole flours but decreased TPC, flavonoid content, antioxidant activities, and phenolic acid concentrations for three varieties. Bread-making steps including fermentation and baking had positive effects on phenolic antioxidants, especially for the soluble fractions. Some soluble phenolic acids were incorporated into Maillard reaction products. Simulated digestion released more soluble trans-ferulic acid than chemical extraction from bread (17.69 to 102.71 μg/g), cookie (15.81 to 54.43 μg/g), and pasta (4.88 to 28.39 μg/g). Colon fermentation further released phenolics from the food matrix. In general, phenolics in whole wheat can be well retained from farm to fork and exhibit considerable bioaccessibility in the human digestive tract. Partial least square (PLS) models were successfully developed using UV-Vis spectra to predict TPC (R²-calibration=0.89, and R²-validation=0.89) and trans-ferulic acid (R²-calibration=0.82, and R²-validation=0.85) in wheat extracts. Moreover, a simpler NIR model that can directly predict the TPC (R²-calibration=0.92, and R²-validation=0.90) of whole wheat flour was also established. Breeding programs that require fast screening and selection of wheat lines with enriched phenolic compounds will greatly benefit from these new techniques.
Keywords: Wheat antioxidant; Phenolic acid; Processing effects; Digestion; Rapid quantification